Recommender System for Sentiment Analysis using Machine Learning Models - et. al., A. Naresh, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In recent years, with the rapid growth of Internet technology, online shopping has become a rapid way for users to purchase and consume desired products. Large volume of user-generated content on social media sites like twitter has resulted in tweet sentiment analysis. Sentiment analysis supports as base for decision support systems and recommendation systems and it becomes an essential tool on online platforms to extract the information on user emotional state to improve user satisfaction. This paper proposes an effective sentiment analysis recommender system framework using machine learning models.